Pitfall in the Diagnosis of Diabetes Insipidus and Pregnancy. (27th July 2017) - Sum, Melissa; Fleischer, Jessica B.; Khandji, Alexander G.; Wardlaw, Sharon L.
Abstract : Diabetes insipidus (DI) during pregnancy and the perinatal period is an uncommon medical problem characterized by polyuria and excessive thirst. Diagnosis of DI may be overlooked in the setting of pregnancy, a time when increased water intake and urine output are commonly reported. We report two cases: one of transient DI in a young woman during her third trimester of twin pregnancy in association with acute fatty liver and hypertension and one of postpartum DI secondary to Sheehan syndrome from rupture of a splenic artery aneurysm. These cases illustrate the spectrum with which DI related to pregnancy and delivery can present and highlight the difficulty in making the diagnosis since the symptoms are often initially overlooked.